The potential of polyphenols from natural ingredients against SARS-CoV-2 infection: A review - Hendrayana, Made Agus; I Made Jawi; Dewa Made Sukrama; Dewa Ngurah Suprapta (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2021)
All countries in the world are facing the coronavirus disease-19 (COVID-19) pandemic which has resulted in various crises. To date, there is no effective treatment in controlling COVID-19. Many clinical trials of approved drugs against COVID-19 were conducted. However, the results were inconclusive, even severe adverse effects were reported. The new effective drugs are therefore urgently needed. Herbal medicines have been widely used by community to enhance the body immune system during COVID-19 pandemic. Polyphenols are large group of active compounds found in the natural ingredients. These compounds have been proven to have biological activity against various pathogen infections including viral infection. During COVID-19 pandemic, various polyphenol compounds from various medicinal plants have been investigated for their activity against severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) both in silico and in vitro. Among the polyphenols investigated, some of them namely papyriflavonol, catechin gallate, gallocatechin gallate, luteolin, quercetin, tangeretin, naringenin, herbacetin, emodin, eriodyctiol, fenoterol, baicalin, myricetin, quercetagetin exhibited strong activity against SARS-CoV-2. The possibilities of mechanism of actions as antiSARS-CoV-2 of these polyphenols were 1) bind to the N protein causing the inhibition of viral transcription and replication; 2) inhibit the binding of S protein to ACE2 receptors preventing the entry of the virus into the host cells; 3) inhibit 3CLpro function inhibiting the viral transcription and maturation; and 4) bind directly to the ACE2 receptor. In conclusion, some polyphenol compounds from nature ingredients are potential to develop to be future antiSARS-CoV-2. However, further the pre-clinical and clinical studies are required to strengthen existing evidence.